Julio César Galtero : [interview]. - Peicovich, Esteban (Colección Los Palabristas, 2007)
Esteban Peicovich reads a text by Gabriel Garcia Marquez, written in response to the dictionary of Spanish language actual use. Peicovich interviews journalist, writer, and translator Julio César Galtero. Galtero was born on June 6th, 1933 in Buenos Aires, Argentina. He translates English and French and currently directs literary workshops. He funded and directed the editorial Hogar Obrero. Galtero recounts how he began to love literature. He tells of the beginning of his education and of works he read.